Evaluation of the Impact of Timeliness of Care on Patient Experience in Suspected Lung Cancer: A Mixed-methods Study - Mackenzie, Tea; Nash, Jessica; Brims, Fraser (Asian Pacific Journal of Cancer Nursing, 2025)
Background: Lung cancer has the highest burden of cancer in Australia and delays in healthcare can significantly worsen outcomes and cause psychological harm. Australian Optimal Care guidelines recommend a 14-day interval between primary care referral and an appointment with a specialist, however, many healthcare providers are not currently meeting this target. The aim of this pilot study was to assess the patient experience during the interval between referral from primary care to being seen in tertiary care. Methods: We recruited patients with suspected lung cancer referred to a tertiary respiratory clinic. A questionnaire was conducted including Likert-style questions to understand patient perspectives of timeliness, coordination, and communication regarding the early stages of lung cancer care. Additional open-ended questions were included to expand the understanding of patients’ perspectives. Results: The questionnaire was completed by 37 of 52 eligible participants (71%), the median age of participants was 69 years old (IQR 15.5-33.5) and the most common diagnosis was lung adenocarcinoma. Overall, patients reported a positive perception of timeliness of care, despite wait time of median 25 (IQR 15.5-33.5) days. Just one participant stated they were aware of a timeliness clinical guideline. The most common stressors reported by patients were ‘fear of the unknown’ and ‘waiting.’ Conclusions: There appears a paradox in perception of expected wait time within the healthcare system and reported concerns by individuals with suspected lung cancer. Awareness of timeliness guidelines is poor. There is scope for interventions such as improved information resources and access to earlier telehealth appointments to impact on patient reported satisfaction.